Investigation on the Thermoluminescence Properties of KGdF4:Sm3+ Polycrystalline - Do, Phan Van (VNU Journal of Science: Mathematics - Physics, 2020)
KGdF 4 polycrystalline doped with the different concentration of Sm 3+ ions were synthesized by hydrothermal technique. Thermoluminescence (TL) glow curves of samples were measured in the range from 50 o C to 400 o C after irradiating beta, neutron and X-ray radiations. The response of TL intensity to impurity concentration and neutron dose were studied in detail. The TL kinetic parameters such as activation energy ( E ) and frequency factor ( s ) were estimated by using the method of heating rate variation.